Development of enhancer trap lines for functional analysis of the rice genome - Changyin Wu; Xiangjun Li; Wenya Yuan; Guoxing Chen; Andrzej Kilian; Juan Li; Caiguo Xu; Xianghua Li; Dao‐Xiu Zhou; Shiping Wang; Qifa Zhang (2003)
Summary Enhancer trapping has provided a powerful strategy for identifying novel genes and regulatory elements. In this study, we adopted an enhancer trap system, consisting of the GAL4/VP16–UAS elements with GUS as the reporter, to generate a trapping population of rice. Currently, 31 443 independent transformants were obtained from two cultivars using Agrobacterium ‐mediated T‐DNA insertion. PCR tests and DNA blot hybridization showed that about 94% of the transformants contained T‐DNA insertions. The transformants carried, on average, two copies of the T‐DNA, and 42% of the transformants had single‐copy insertions. Histochemical assays of approximately 1000 T 0 plants revealed various patterns of the reporter gene expression, including expression in only one tissue, and simultaneously in two or more tissues. The expression pattern of the reporter gene in T 1 families corresponded well with the T 0 plants and segregated in a 3 : 1 Mendelian ratio in majority of the T 1 families tested. The frequency of reporter gene expression in the enhancer trap lines was much higher than that in gene trap lines reported previously. Analysis of flanking sequences of T‐DNA insertion sites from about 200 transformants showed that almost all the sequences had homology with the sequences in the rice genome databases. Morphologically conspicuous mutations were observed in about 7.5% of the 2679 T 1 families that were field‐tested, and segregation in more than one‐third of the families fit the 3 : 1 ratio. It was concluded that GAL4/VP16–UAS elements provided a useful system for enhancer trap in rice.